Experimental study on the failure of electronic expansion valve of a R290 split room air conditioner. (April 2020) - Li, Jinbo; Du, Yanjun; Wu, Jianhua; Lin, Jie; Wang, Che
Abstract: With the extensive use of room air conditioners, their refrigerants have a greater impact on the environment. Among many alternative refrigerants, R290 is environmentally friendly and energy-saving. Furthermore, the dynamic characteristics of R290 split room air conditioners are different from those of HFCs and HCFCs air conditioners. In previous research of R290 split room air conditioners, abnormal system parameters frequently occurred in heating and defrosting process. In this paper, the abnormal phenomena are determined to be caused by the oil blockage of throttle component. Especially, the failure often leads to safety problems of air conditioner. In addition, the abnormal phenomena of a R290 split room air conditioner was reproduced in the enthalpy difference chamber. The influence factors of the failure were studied experimentally and the experimental results showed that the oil blockage of EEV are mainly affected by the working conditions, the type of lubricating oil and the opening of EEV, which will provide experimental basis for further mechanism analysis and solution.